Microhardness of glass ionomer cements indicated for the ART technique according to surface protection treatment and storage time - Luciana Keiko Shintome; Marcos Paulo Nagayassu; Rebeca Di Nicoló; Silvio Issáo Myaki (Sociedade Brasileira de Pesquisa Odontológica, 2009)
The aim of this study was to assess the microhardness of 5 glass ionomer cements (GIC) - Vidrion R (V, SS White), Fuji IX (F, GC Corp.), Magic Glass ART (MG, Vigodent), Maxxion R (MR, FGM) and ChemFlex (CF, Dentsply) - in the presence or absence of a surface protection treatment, and after different storage periods. For each GIC, 36 test specimens were made, divided into 3 groups according to the surface protection treatment applied - no protection, varnish or nail varnish. The specimens were stored in distilled water for 24 h, 7 and 30 days and the microhardness tests were performed at these times. The data obtained were submitted to the ANOVA for repeated measures and Tukey tests (α = 5%). The results revealed that the mean microhardness values of the GICs were, in decreasing order, as follows: F > CF = MR > MG > V; that surface protection was significant for MR, at 24 h, without protection (64.2 ± 3.6a), protected with GIC varnish (59.6 ± 3.4b) and protected with nail varnish (62.7 ± 2.8ab); for F, at 7 days, without protection (97.8 ± 3.7ab), protected with varnish (95.9 ± 3.2b) and protected with nail varnish (100.8 ± 3.4a); and at 30 days, for F, without protection (98.8 ± 2.6b), protected with varnish (103.3 ± 4.4a) and protected with nail varnish (101 ± 4.1ab) and, for V, without protection (46 ± 1.3b), protected with varnish (49.6 ± 1.7ab) and protected with nail varnish (51.1 ± 2.6a). The increase in storage time produced an increase in microhardness. It was concluded that the different GICs, surface protection treatments and storage times could alter the microhardness values.